Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) \(\left(x-y\right)^2+2xy\)
\(=x^2-2xy+y^2+2xy\)
\(=x^2+y^2\left(đpcm\right)\)
b) \(\left(x-y\right)^2+4xy\)
\(=x^2-2xy+y^2+4xy\)
\(=x^2+2xy+y^2\)
\(=\left(x+y\right)^2\left(đpcm\right)\)
a, Ta có:\(\left(x-y\right)^2=x^2-2xy+y^2\)
\(\Leftrightarrow x^2+y^2=\left(x-y\right)^2+2xy\left(ĐCCM\right)\)
b,Ta có:\(\left(x+y\right)^2=x^2+2xy+y^2\)
\(\Leftrightarrow\left(x+y\right)^2=x^2-2xy+4xy+y^2\)
\(\Leftrightarrow\left(x+y\right)^2=\left(x-y\right)^2+4xy\left(ĐCCM\right)\)
Vt = (x - y)^2 + 4xy = x^2 -2xy + y^2 + 4xy = x^2 +2xy+ y^2 = ( x+y)^2 = VP
=> ĐPCM
b, (x + y)^2 = ( x - y)^2 + 4xy = 5^2 + 4.3 = 25 + 12 = 37
a)
VT=(x-y)2+4xy=x2-2xy+y2+4xy=x2+2xy+y2=(x+y)2=VP
=> (x-y)2+4xy=(x+y)2
b) (x+y)2=x2+2xy+y2
=x2-2xy+y2+4xy
=(x-y)2+4xy
=52+4.3
=25+12
=37
Ah đã có mặt :)
\(\left(1+x^2\right)\left(1+y^2\right)+4xy+2\left(x+y\right)\left(1+xy\right)\)
\(=1+x^2+y^2+x^2y^2+4xy+2\left(x+y\right)\left(1+xy\right)\)
\(=\left(x^2+2xy+y^2\right)+\left(x^2y^2+2xy+1\right)+2\left(x+y\right)\left(1+xy\right)\)
\(=\left(x+y\right)^2+\left(1+xy\right)^2+2\left(x+y\right)\left(1+xy\right)\)
\(=\left(x+y+xy+1\right)^2\)là số CP (đpcm)
a ) Ta có :
\(\left(x+y\right)^2-\left(x-y\right)^2\)
\(=\left[\left(x+y\right)-\left(x-y\right)\right]\left[\left(x+y\right)+\left(x-y\right)\right]\)
\(=\left(2x\right)\left(2y\right)\)
\(=4xy\)
\(\Rightarrow DPCM\)
1A = x^2 + 3x + 3
A= x^2 + 2.x.1,5 + 2.25 + 0,75
A = (x+1,5)^2 +0,75
=> Min A = 0,75 khi x= 1,5
2 Đặt A=x2+5y2+2x−4xy−10y+14
A=(x2−4xy+4y2)+(2x−4y)+1+y2−6y+9+4
A=(x−2y)2+2(x−2y)+1+(y−3)2+4
A=(x−2y+1)2+(y−3)2+4≥4>0
⇒A>0(đpcm)
a) \(2x^2y^2-\frac{4}{3}x^2y+2xy\)
\(=xy\left(2xy-\frac{4}{3}x+2\right)\)
b) 2xy2.(x + 5y) - 4xy(5y + x)
= (5y + x)(2xy2 - 4xy)
= 2xy(5y + x)(y - 2)
c) 25 - 4x2 - y2 + 4xy
= 25 - (4x2 - 4xy + y2)
= 52 - (2x + y)2
= (5 - 2x - y)(5 + 2x + y)
d) x2 + 4x - 2xy - 4y +y2
= (x2 - 2xy + y2) + (4x - 4y)
= (x - y)2 + 4(x - y)
= (x - y)(x - y + 4)
e) 12y3 - 3x2y + 12xy - 12y
= 3y(4y2 - x2 + 4x - 4)
= 3y[4y2 - (x - 2)2]
= 3y(2y - x + 2)(2y + x - 2)
f) 64x4 + y4
= (8x2)2 + 16x2y2 + y4 - 16x2y2
= (8x2 + y2)2 - (4xy)2
= (8x2 + y2 - 4xy)(8x2 + y2 + 4xy)
a) \(2x^2y^2-\frac{4}{3}x^2y+2xy\)
b) \(2xy^2\left(x+5y\right)-4xy\left(5y+x\right)\)
\(=\left(x+5y\right)\left(2xy^2-4xy\right)\)
\(=2\left(x+5y\right)\left(xy^2-2xy\right)\)
c) \(25-4x^2-y^2+4xy\)
\(=25-\left(4x^2+y^2-4xy\right)\)
\(=5^2-\left[\left(2x\right)^2-2.2x.y+y^2\right]\)
\(=5^2-\left(2x-y\right)^2\)
\(=\left(5-2x+y\right)\left(5+2x-y\right)\)
d) \(x^2+4x-2xy-4y+y^2\)
\(=\left(x^2-2xy+y^2\right)+\left(4x-4y\right)\)
\(=\left(x-y\right)^2+4\left(x-y\right)\)
\(=\left(x-y\right)\left(x-y\right)+4\left(x-y\right)\)
\(=\left(x-y\right)\left(x-y+4\right)\)
e) \(12y^3-3x^2y+12xy-12y\)
f) \(64x^4+y^4\)
\(=\left(8x^2\right)^2+16x^2y^2+\left(y^2\right)^2-16x^2y^2\)
\(=\left(8x^2+y^2\right)^2-\left(4xy\right)^2\)
\(=\left(8x^2+y^2+4xy\right)\left(8x^2+y^2-4xy\right)\)
\(VT=\left(x-y\right)^2+4xy=x^2-2xy+y^2+4xy\)
\(=x^2+2xy+y^2=\left(x+y\right)^2=VP\)
p/s: chúc bạn học tốt
(x-y)2+4xy =x2-2xy+y2 +4xy=x2+2xy+y2=(x+y)2